5(x-4)-3=-2(x-3)

Simple and best practice solution for 5(x-4)-3=-2(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-4)-3=-2(x-3) equation:


Simplifying
5(x + -4) + -3 = -2(x + -3)

Reorder the terms:
5(-4 + x) + -3 = -2(x + -3)
(-4 * 5 + x * 5) + -3 = -2(x + -3)
(-20 + 5x) + -3 = -2(x + -3)

Reorder the terms:
-20 + -3 + 5x = -2(x + -3)

Combine like terms: -20 + -3 = -23
-23 + 5x = -2(x + -3)

Reorder the terms:
-23 + 5x = -2(-3 + x)
-23 + 5x = (-3 * -2 + x * -2)
-23 + 5x = (6 + -2x)

Solving
-23 + 5x = 6 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-23 + 5x + 2x = 6 + -2x + 2x

Combine like terms: 5x + 2x = 7x
-23 + 7x = 6 + -2x + 2x

Combine like terms: -2x + 2x = 0
-23 + 7x = 6 + 0
-23 + 7x = 6

Add '23' to each side of the equation.
-23 + 23 + 7x = 6 + 23

Combine like terms: -23 + 23 = 0
0 + 7x = 6 + 23
7x = 6 + 23

Combine like terms: 6 + 23 = 29
7x = 29

Divide each side by '7'.
x = 4.142857143

Simplifying
x = 4.142857143

See similar equations:

| (7x^2+22x-4)-(5x^2+3x-39)= | | (x-4)(x+8)(x-(2x+3i))(x-(2x-3i))=0 | | (x-3)-4=(x-5) | | 9+4(x+1)=11 | | w-2xy=2xz | | -2/3x=-5/9 | | 16(v+1)-4v=3(4v+3)-18 | | 4x+3=3x-15 | | 1000/x=19.3 | | 9+5(x+1)=11 | | 18-4x=-2(2x+6) | | 16-7x=-12 | | 2x(2x-7)=-12 | | 4*x=-19 | | -15-2x=16-(3x-y) | | 5r+6=4r-2(r-3) | | 1/2=3x=1/9 | | y+14.6=13.75 | | D^3=1932367.15findtheD | | 3/8-x=5/6 | | 14/39*3/4 | | -3(2x-9)=42 | | x-3/4-4=x-8/3 | | (2+y)(2x-5)(3a-8)(5b+27)=0 | | D^3=1932367.15 | | -2a-7(1-5a)=158 | | (2m-4)X=(2m+2) | | 9=4n+-59 | | 12=3(4x-19) | | h=-16t^2+96t+80 | | 5n+16=81 | | 8(2y^2-7y+4)-7(2y^2-2y+6)= |

Equations solver categories